EFFECTIVENESS OF USING HERBAL PLANT-BASED FEED ADDITIVES ON BROILER PERFORMANCE - Hidayat, Muhammad Nur; Yulianingsih, Yulianingsih (JURNAL NUKLEUS PETERNAKAN, 2024)
Due to the regulation prohibiting the use of Antibiotic Growth Promoters (AGP), it is essential to explore alternative solutions for feed additives in the broiler industry. One promising approach is to utilize herbal plants as feed additives to enhance the performance and quality of broilers. This study aims to evaluate the effectiveness of herbal plant-based feed additives, specifically fermented garlic, cinnamon, and betel leaves, on the performance and quality of broiler carcasses. This study employed a completely randomized design (CRD) featuring four treatments and five replications. For a duration of 30 days, the treatments administered to the broilers included: P0 (control), P1 (herbal concoction at 1.5 ml per 500 ml of water), P2 (herbal concoction at 2.5 ml per 500 ml of water), and P3 (herbal concoction at 3.5 ml per 500 ml of water).The variables measured in this study included feed consumption, body weight gain, and feed conversion. The administration of herbal medicine did not have a significant effect (P > 0.05) on feed consumption, body weight gain, or feed conversion in broilers. However, the level of herbal medicine administration showed some trends: P3 (3.5 ml herbal medicine per 500 ml of water) was associated with better feed consumption and body weight gain, while P2 (2.5 ml herbal medicine per 500 ml of water) indicated a tendency for improved feed conversion.